Selected Aspects of Information Management in Extraordinary Situations - Pietrek, Grzegorz; Jałowiec, Tomasz (Roczniki Nauk Społecznych, 2025)
The aim of this article is to identify the impact of information management on the decision-making process in emergency situations. The research questions were centered around determining the relevance of information in decision-making processes and the relevance of issues related to information valuation and ‘information behavior.’ The research methodology is extensive – mainly theoretical methods such as literature analysis, act analysis, synthesis, abstraction, induction, deduction, comparison, or inference were used in the research. The conclusions of the research indicate the need to ensure an efficient circulation of information for the functioning of the authorities responsible for state security in crisis situations. In a situation that threatens security, decisions need to be worked out in order to take such actions that will restore the pre-crisis state.